1999
DOI: 10.1038/sj.jp.7200201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dexamethasone on Lymphocyte Subpopulations in Premature Infants with Bronchopulmonary Dysplasia

Abstract: OBJECTIVE:This study was designed to determine the effect of dexamethasone treatment on peripheral blood lymphocyte counts and subpopulations in premature infants with bronchopulmonary dysplasia (BPD). STUDY DESIGN:Peripheral blood lymphocyte subpopulations in 12 premature infants with BPD were analyzed before treatment with a 6-week course of dexamethasone (day 0), on days 3 and 10 of treatment, and 2 weeks after discontinuing dexamethasone therapy (day 56). Lymphocyte immunophenotypes were determined using d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
0
11
1
Order By: Relevance
“…This alteration in lymphocyte subpopulations may account for the clinically beneficial anti-inflammatory effect of dexamethasone in the treatment of BPD. It may also increase the susceptibility of these infants to infection, especially Candida sepsis [182,183].…”
Section: Anti-inflammatory Effects Of Corticosteroids In Bpdmentioning
confidence: 99%
“…This alteration in lymphocyte subpopulations may account for the clinically beneficial anti-inflammatory effect of dexamethasone in the treatment of BPD. It may also increase the susceptibility of these infants to infection, especially Candida sepsis [182,183].…”
Section: Anti-inflammatory Effects Of Corticosteroids In Bpdmentioning
confidence: 99%
“…Dexamethasone may directly inhibit T cell proliferation (7), induce apoptosis (8), promote long-lasting changes in the T cell receptor v␤ repertoire (9), or decrease the CD4/CD8 ratio in infants with BPD (10). Dexamethasone also influences gene expression of cytokines and various functions of antigen pre-senting cells (APC), including B cells, dendritic cells, and monocytes/macrophages (11)(12)(13).…”
mentioning
confidence: 99%
“…In the study reported here we found that the absolute number of lymphocytes was lower among infants with RDS who developed BPD compared with those who did not over the first 2 weeks of life and that the percentage and absolute number of CD4 + T cells were similarly affected. Parimi et al 11 have reported that premature infants given a 6-week course of dexamethasone had suppressed lymphocyte percentage and number and reduced CD4 + T cell percentage and number after 3 days of treatment compared with baseline values. Our study suggests that low lymphocyte numbers, especially CD4 + T cell numbers, may be intrinsically linked with susceptibility to BPD.…”
Section: Discussionmentioning
confidence: 99%
“…10 Conversely but interestingly, postnatal dexamethasone treatment of premature infants with BPD significantly decreases the percentage and absolute number of lymphocytes, T cells, specifically CD4 + T cells, and therefore the CD4 + /CD8 + ratio. 11 In addition, postnatal dexamethasone treatment in BPD increases B cells transiently and does not affect CD8 + T cells. However, there is little information on alterations in the lymphocyte subpopulations that might characterize the development of BPD, especially in the absence of clinical infection.…”
mentioning
confidence: 97%